Correction: One pot ligand exchange method for a highly stable Au-SBA-15 catalyst and its room temperature CO oxidation - Soni, Yogita; Kavya, I; Ajithkumar, T. G; Vinod, C. P (Chemical communications (Cambridge, England), 2018)
Correction for 'One pot ligand exchange method for a highly stable Au-SBA-15 catalyst and its room temperature CO oxidation' by Yogita Soni et al., Chem. Commun., 2018, DOI: 10.1039/c8cc06887a.Correction for 'One pot ligand exchange method for a highly stable Au-SBA-15 catalyst and its room temperature CO oxidation' by Yogita Soni et al., Chem. Commun., 2018, DOI: 10.1039/c8cc06887a.